Mortalitas dan bobot badan tiga strain ayam broiler pada kepadatan kandang yang berbeda - Asep Setiaji; Nurfaizin; Binti Ma’rifah; Lilik Krismiyanto (Politeknik Negeri Jember, 2021)
The aim of this study was to analyze the effects of strain, density and their interaction on mortality and body weight of broiler chicken raised in the closed houses. The data was obtained from 60 broiler farms in the Central Java province. Three strains were Cobb, CP 707, and Loghman. The density level was classified into three groups: £10, >10 to <15, and ³ 15 birds/m2. Parameters observed were mortality and body weight in the first week to the fifth week (M1, M2, M3, M4, and M5) and (BB1, BB2, BB3, BB4 dan BB5), respectively. Test of significance effect for strain and density was performed using Mixed procedure of Statistical Analysis System (SAS) University Edition V.6p.2. software. The results showed that density was significant (P<0,01) on the first week (M1), their interaction was (P<0,01) on M1 and (P<0,05) on the fourth week (M4), but not significant on body weight. The conclusion from this study there was an interaction between genetic and environment on mortality one week after chick in and nearly harvesting.